ANALISIS PERSEPSI MAHASISWA EKONOMI SYARIAH UIN RADEN FATAH PALEMBANG TERHADAP PENGARUH PERGERAKAN IHSG DALAM KEPUTUSAN INVESTASI SAHAM - Zahira Indah Kurnia; Peny Cahaya Azwari (CV. Cendikiawan Muda Sriwijaya, 2026)
The development of the Indonesian capital market, as reflected in the movement of the Jakarta Composite Index (JCI), is one of the main indicators often used in making decisions regarding stock investments. Students, as a young generation beginning to understand the world of investment, have varying views regarding the influence of JCI movements on their investment decisions. This study aims to evaluate the views of students in the Sharia Economics Study Program at the Raden Fatah State Islamic Institute in Palembang regarding the impact of JCI movements on their stock investment decisions. This study employed a qualitative approach with descriptive methods. Data collection techniques included in-depth interviews, direct observation, and document searches with students who already understand or are involved in stock investment. The data obtained were then analyzed using data reduction, data presentation, and conclusion drawing techniques. This study shows that most students consider the JCI to be an important indicator for monitoring the condition of the capital market and the Indonesian economy. JCI movements are one of the factors considered in making investment decisions because they are considered to provide an overview of market trends, risk levels, and profit opportunities from investments. However, students not only pay attention to the movement of the JCI, but also take into consideration various other factors such as financial literacy levels, fundamental company analysis, the national economic situation, information from the media, and advice provided by the investment community. The findings of this study indicate that students have a fairly good understanding of the role of the JCI in stock investment, but there is still a need for increased capital market education to help them make more rational investment decisions based on adequate information.